PENGARUH KEMAMPUAN KERJA, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI LINGKUP SMK KESEHATAN BAKTI INDONESIA MEDIKA NGAWI - Permana, Yudha Indra (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2015)
The aim in this study was to determine the significance of the effect of work ability, motivation and compensation to employee performance in SMK Kesehatan Bakti Indonesia Medika Ngawi. Data collection techniques in the form of a list of questions submitted to the permanent teachers of SMK Kesehatan Bakti Indonesia Medika Ngawi as primary data and the literature as secondary data. Number of census research as much as 38 permanent teachers and all researched. Data analysis method used is the classic assumption test, hypothesis test Moderated Regression Analysis. Results of research on work ability significantly influence employee performance SMK Kesehatan Bakti Indonesia Medika Ngawi (0,019 < 0,05), so the H1 proven true. Motivation significant effect on employee performance SMK Kesehatan Bakti Indonesia Medika Ngawi (0,040 < 0,05), so the H2 proven true. Compensation significant effect on employee performance SMK Kesehatan Bakti Indonesia Medika Ngawi (0,003 < 0,05), so the H3 proven true. Limitations of this study target population of this research is that small-scale population that is limited to employees still in SMK Kesehatan Bakti Indonesia Medika Ngawi so that research results can only be generalized to the population group being targeted. Keywords: Work Ability, Motivation, Compensation and Performance.